The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10147-014-0739-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing biopsy procedures during colposcopy for women with abnormal cervical cancer screening results: a multicenter prospective study

Abstract: Our data suggest that at least two colposcopy-directed biopsies should be taken for histological diagnosis. Random biopsies and ECC are recommended for special populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…However, this finding is limited by the small number (n = 29) of women whose examination reports included the transformation zone. Other studies have shown a higher benefit of ECC in this patient population [15,26]. The accuracy was higher (69.2%) for the 13 cases investigated preoperatively with ECC alone.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…However, this finding is limited by the small number (n = 29) of women whose examination reports included the transformation zone. Other studies have shown a higher benefit of ECC in this patient population [15,26]. The accuracy was higher (69.2%) for the 13 cases investigated preoperatively with ECC alone.…”
mentioning
confidence: 57%
“…This assumption is also borne out by other studies which have showed increased sensitivity when several biopsies are taken compared to when only one biopsy is obtained [15]. The highest sensitivity for the detection of high-grade dysplasia as reported in a study by Wentzensen et al was 95.6 % after taking three biopsies; the figure dropped to 85.6 % after two biopsies and to 60.6 % if only one biopsy was taken [20].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have reported that colposcopy‐directed biopsies are suboptimal and fail to detect cervical intraepithelial neoplasia grade 2 or worse (CIN2+) in 26–57% of cases . Some authors have found that an increase in the number of biopsies taken from colposcopy‐positive areas improves the detection of high‐grade dysplasia . Others have shown that taking additional biopsies from colposcopy‐negative areas increases the detection of CIN2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Las principales limitaciones durante el proceso de diagnóstico cuando nos enfrentamos a una citología alterada son 1) la interpretación correcta de los hallazgos a la colposcopia y 2) el muestreo apropiado de cualquier lesión sospechosa. De hecho, la ausencia de una lesión que explique una citología alterada aumenta el riesgo de mal diagnóstico y sobre-tratamiento, a pesar de la adición de ECC o el uso de biopsias al azar [10,11]. El estándar de oro para indicar una conización, lo constituye la confirmación histológica de NIE2+.…”
Section: Materials Y Métodosunclassified